Altered Calcium Signaling Following Traumatic Brain Injury - Weber, John T. (Frontiers in Pharmacology, 2012)
Cell death and dysfunction after traumatic brain injury (TBI) is caused by a primary phase, related to direct mechanical disruption of the brain, and a secondary phase which consists of delayed events initiated at the time of the physical insult. Arguably, the calcium ion contributes greatly to the delayed cell damage and death after TBI. A large, sustained influx of calcium into cells can initiate cell death signaling cascades, through activation of several degradative enzymes, such as proteases and endonucleases. However, a sustained level of intracellular free calcium is not necessarily lethal, but the specific route of calcium entry may couple calcium directly to cell death pathways. Other sources of calcium, such as intracellular calcium stores, can also contribute to cell damage. In addition, calcium-mediated signal transduction pathways in neurons may be perturbed following injury. These latter types of alterations may contribute to abnormal physiology in neurons that do not necessarily die after a traumatic episode. This review provides an overview of experimental evidence that has led to our current understanding of the role of calcium signaling in death and dysfunction following TBI.